2017
DOI: 10.1016/j.fertnstert.2017.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the opioid system on the reproductive axis

Abstract: Endogenous opioids, first described more than 40 years ago, have long been recognized for their main role as important neuromodulators within the central nervous system. More recently endogenous opioids and their receptor have been identified in a variety of reproductive and nonreproductive tissues outside the central nervous system. Their role within these tissues and organs, however, is only incompletely understood. In the central nervous system, endogenous opioids inhibit pulsatile GnRH release, in part med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 61 publications
1
23
0
4
Order By: Relevance
“…Finally, the opioid system is known to be involved in regulating carbohydrate metabolism and immune system functions in the periphery (62,63). This is consistent with the phosphorylation changes we observe in the metabolic enzymes like PGK1 and PGK2, which are implicated in an important step of the glycolysis (64), and hence in sperm fertility (65).…”
Section: Molecular and Cellular Proteomics 1813 S127supporting
confidence: 86%
“…Finally, the opioid system is known to be involved in regulating carbohydrate metabolism and immune system functions in the periphery (62,63). This is consistent with the phosphorylation changes we observe in the metabolic enzymes like PGK1 and PGK2, which are implicated in an important step of the glycolysis (64), and hence in sperm fertility (65).…”
Section: Molecular and Cellular Proteomics 1813 S127supporting
confidence: 86%
“…The opioid system manages the endocrine function of β-cells [40]. Within the pancreas, EOPs result in insulin secretion via the paracrine and the intracrine mechanisms [41]. Opioid activity can perform an important role in the physiopathology of hyperinsulinemia in hyperandrogenic women [38].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the etiology of her amenorrhea was weight loss in the context of systemic illness, compounded by narcotics. Narcotic analgesics shut off the GnRH pulse generator and the pituitary-ovarian axis is also thus shut off [7], a finding that was illustrated many years ago [8]. Using electrodes implanted in the mediobasal hypothalamus of the ovariectomized rhesus monkey to record multiunit activity, with simultaneous measurement of serum LH, it was shown that a single 2-min intravenous infusion of morphine (2 mg per kg body weight) shuts down multiunit electrical activity of the pulse generator and the corresponding LH pulses, this effect lasting at least 4 h. The outcome is the same as that of endogenous opioids such as β-endorphin that are produced in response to stress and exercise.…”
Section: Casementioning
confidence: 99%